A phenomenological exploration on the challenges of elite triathletes' academic performance - Jaudian, Kelsey Claire M. 2001-
The current body of research has primarily focused on the challenges of athletes who engage in single sports events, and few of them tackle the challenges of elite athletes. Hence, this qualitative study aims to look into the challenges elite triathletes experience in terms of their academic performance. A phenomenological interview consisting of open-ended questions was conducted with five elite triathletes who are enrolled in college here in the Philippines. The results showed five themes: Athlete-Student Identity, Difficulty in Managing Time. Tug-of-War between Academics and Sports, Challenges in Transitioning, and Stigma on Athletes. These results showed that these elite triathletes have a strong athlete-student identity due to being at the top of their sport, which results in them having a hard time balancing both their academic and sporting careers.